EVALUATION OF ROAD CONSTRUCTION POLICY IN HEGARMANAH VILLAGE CICANTAYAN DISTRICT SUKABUMI REGENCY - Nurul Syahida; Dine Meigawati; M. Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2022)
The road condition of Hegarmanah Village is dominated by dirt-based roads and damaged road conditions, which can result in disruption of local community mobilization. The purpose of this study is to find out how to evaluate the road development policy of Hegarmanah Village, Cicantayan District, Sukabumi Regency. This research uses the theory of William N. Dunn, 2018. The research method uses qualitative research methods. Data collection techniques use observation, interviews and documentation. Data validation used triangulation of sources, techniques, and time, data analysis using data condensation, data display, and drawing conclusions. The results showed that the Hegarmanah Village road construction policy related to the desired results has not been fully achieved, there is still a lot of development that has not been carried out, due to the refocusing of the budget, namely the budget for activities in 2021 cut for handling Covid-19, therefore there are still many activities that should be carried out in 2021 to be not carried out due to budget cuts that focus activities on handling Covid-19. 19. Each development activity is carried out based on a priority scale resulting from deliberations and mutual agreements of the community in accordance with the regulations and budget obtained by Hegarmanah Village. In conclusion, regarding the benefits of the Village road construction policy, it has not been distributed evenly throughout the area in Hegarmanah Village, there are still many damaged road conditions and even based on land that requires repairs and development.